New Technologies in Protective Coatings - Giudice, Carlos; Canosa, Guadalupe (IntechOpen, 2017)
Materials are at the center of all technological advances; it is evident in considering the spectacular progress that has been made in fields as diverse as engineering, medicine, biology, etc. Materials science and technology must develop researches allowing the generation of new methods of protection to reduce fundamentally the losses of human life as well as the economic ones. The former are impossible of quantifying, while the latter are highly significant; thus, only those derived from corrosive processes in their different forms reach, in technologically developed countries, about 4% of the Gross National Product (GNP), while those derived from fire action range from 0.5 to 1.0% of the mentioned GNP. The book, in the different chapters, displays original systems of superficial protection and of low environmental impact to minimize the losses by corrosion and the fire action.